The Flashing T-Shirt Company - Paulus, Celestina; Pidu, Dyna Nurmiana; Mokitang, Hartley; Abd Wahab, Juraisyah (2014)
My name is Celetina Paulus and I am the General Manager of The Flashing T-Shirt Company. I am writing to introduce THE FLASHING COMPANY, wherein our company provides specific LED Flashing T-Shirt. Our company prepare product that follow the demand by the customer Our main office is located at Kota Kinabalu, Sabah. We estimate to start up our business on May 2015. With the reference of government of Sabah there have 3.15 million people in Sabah. On the other hand, based on the scientific research that we had and the population of people in Sabah, we can say that our product can be one of the creative T-Shirt that bring a new innovation to the younger generation actually. For example, we can wear this T-Shirt when celebrating party such as birthday party, Hari Raya, Christmas and Independent Day. We provide a lot of design of the LED Flashing TShirt following the trend of the party. THE FLASHING T-SHIRT is a new brand in Malaysia that still unknown in market. The main product of our shop is the LED FLASHING T-SHIRT. THE LED FLASHING T-SHIRT is made from 100% cotton. Our product is attractive because The LED Flashing T-Shirt is a light up shirt that flashes to the beat of any music playing around it. Nowadays, all festival paty using sound activated flashing up and down LED light music equalizer T-Shirt. The LED Flashing TShirt is a sound sensitive flashing equalizer shirt, perfect for anyone with a cool mood and a hint of chic. Therefore, we are confident this business has a high potential to expand to the international market.